Broken Prey - Sandford, John (New York Barkley, 2006)
Haunted by a lifetime of unusual memory lapses, Ana begins a new life as librarian of a Denver girls' school, until an encounter with Pierce Rourke brings her face to face with the man who can free her from the past.
Keywords: Murder--Investigation